Pattern of Agricultural Poisoning in District Level Hospital (KYAMC Journal, 2022)
Background: In Bangladesh, acute poisoning is a serious public health issue. Suicide by this manner is rather prevalent. Every area needs a detailed picture of clinical presentation, the most widely utilized hazardous substances, background circumstances, and the result of poisoned patients. The study's goal is to look at the occurrence and outcomes of acute poisoning episodes in Pabna Upazila, Bangladesh. Objective: To find out the chemical types of agricultural poison and out of the acute poisoning cases by agricultural poisons.Materials and Methods: This is a prospective study, carried out in Pabna Sadar Hospital between  April 2019 to December 2019.Results: A total of 120 patients were studied in this study. There were 23 males and 97 females. The average age group for acute poisoning was 15-25 years. The major toxic agent that caused the acute poisoning death was OPC. The average hospital stay was 2-3 days, and 82% of patients were fully recovered and discharged.Conclusion: Acute poisoning cases were more in young age group, female; most of the patient had history of ingestion of OPC and more than two-third cases recovered.KYAMC Journal Vol. 13, No. 03, October 2022: 145-148